Facile Synthesis of the Isoquinoline Alkaloids Doryanine and Oxyhydrastinine - Jangir, Ravi; Gadre, Smita R.; Argade, Narshinha P. (Synthesis, 2014)
Starting from 4,5-(methylenedioxy)homophthalic acid, a concise and efficient synthesis of the isoquinoline alkaloids doryanine and oxyhydrastinine is described via the corresponding homophthalimide utilizing a one-pot regioselective reductive dehydration and catalytic hydrogenation pathway.
Keywords: homophthalic acid; homophthalimide; regioselective reduction; dehydration; isoquinoline alkaloids